Relationship Between Lightning, Precipitation, and Environmental Characteristics at Mid‐/High Latitudes From a GLM and GPM Perspective. Issue 13 (2nd July 2022) - Heuscher, Lena; Liu, Chuntao; Gatlin, Patrick; Petersen, Walter A.
Abstract: This study applies new satellite datasets and methodologies to build on previous research exploring the physical relationship between lightning and precipitation in mid‐/high latitudes. Specifically, 3 years of Geostationary Lightning Mapper and Global Precipitation Measurement Mission core satellite coincident observations are examined to investigate relationships between lightning flash rate and microwave characteristics of convective precipitation features (cPFs) over the Americas and surrounding oceans between ±50° latitude. Mid‐/high latitude cPFs with lightning are characterized by colder temperatures of maximum 30 dBz echo top height and a smaller range of microwave brightness temperatures when compared to the tropics. Brightness temperature characteristics of electrically active cPFs are highly correlated to radar‐diagnosed ice mass and largely insensitive to synoptic‐scale proxies for convective strength and organization. Low flash density cPFs tend to be more sensitive to synoptic‐scale instability and shear than high flash density cPFs. Regional differences in the environmental forcing and characteristics of electrically active cPFs are shown. For example, the elevated terrain surrounding the Amazon River Basin is characterized by stronger vertical updrafts indicated by higher values of normalized CAPE while the La Plata River Basin is characterized by both stronger updrafts and higher values of radar‐diagnosed ice water mass. Plain Language Summary: New satellite‐based lightning observations collected over Earth's mid‐/high latitudes provide opportunities to observe and better understand relationships between lightning and precipitation properties over a larger domain than that of the historically sampled global tropics. Considered at hemispheric scales, newly combined continuously observed lightning data and low‐Earth orbiting precipitation "snapshots" suggest lightning and precipitation relationships derived from tropical observations also hold for the mid‐/high latitudes. Regional nuances are found in the electrical and microwave characteristics of deep convection—mid‐/high latitude convection is characterized by colder 30‐dBz echo top heights (indicating stronger updrafts) and a smaller range of microwave brightness temperatures when compared to the tropics. Large‐scale environments where electrically active convection is observed are also examined. Physical processes tied to deep convection (e.g., lofting of ice or updraft strength) can explain some trends in the satellite‐observed precipitation and lightning data. Regional differences in the percentage of electrically active convection characterized by stronger inferred updrafts and higher derived values of ice are discussed. Key Points: Global precipitation measurement combined with geostationary lightning mapper observations facilitates new investigations of convective precipitation in the mid‐/high latitudes Convective life cycle stage can be inferred by examining flash rate in terms of radar and passive microwave properties Different synoptic environmental influences on observed precipitation/lightning properties are explained by impacts on physical processes